Answer:
d the negatives canceled each other out making it positive
-7z^7(-19z^7) = (-7 x -19) x z^(7 + 7) = 133z^14
Answer:
You cant
Step-by-step explanation:
It can't be beat that's how they get you cause you say to yourself oh i can do this but you can't
Answer:
4. U = 54
5. C=80
Step-by-step explanation:
Basically you move the denominator to the other side and multiply. please take note of the signs(positve, negative)
Here is all I got for you. From the starting expression to the simplest one.
t^2 + 4tv + 4^2 =
t^2 + 4tv + 16 =
t(t + 4v) + 16